Obesity and dyslipidemia in patients with psoriasis treated at a dermatologic clinic in Manaus - Santos,Mônica (2013)
BACKGROUND: Psoriasis is a chronic inflammatory disease of multifactorial etiology, with participation of genetic, autoimmune and environmental factors. Recent studies have demonstrated the role of inflammatory cells and mediators in the pathogenesis of psoriasis, which is now defined as a systemic and autoimmune inflammatory disease that may be associated with other diseases of inflammatory nature. OBJECTIVES: To evaluate the occurrence of obesity and dyslipidemia in patients with psoriasis treated at a dermatology clinic in Manaus. METHODS: We performed a prospective descriptive study to assess the prevalence of obesity and dyslipidemia in patients with psoriasis. Besides the recommended dermatological care, a physical examination was performed to measure weight, height and waist circumference. RESULTS: We included 72 patients, 44 (61.1%) female and 28 (38.9%) male, with a mean age of 51.0 years ± 15.9 years. As for body mass index (BMI), 16 (22.2%) were overweight and 20 (27.8%) were obese. In the analysis of waist circumference in relation to gender, we found that 79.5% of women surveyed had central obesity, a percentage statistically higher than that observed among men (42.9%) at the 5% level of significance (p = 0.001). Regarding the diagnosis of dyslipidemia, 29 (65.9%) females and 22 (78.6%) males showed alterations in lipid profile. CONCLUSIONS: The occurrence of dyslipidemia and obesity in patients with psoriasis can affect life quality and expectancy, increasing the risk of systemic and metabolic diseases, which makes periodic investigation of these comorbidities in patients with psoriasis mandatory.